Massive star cluster formation with binaries. I. evolution of binary populations - Cournoyer-Cloutier, Claude; Sills, Alison; Harris, William E.; Polak, Brooke; Rieder, Steven; Andersson, Eric P.; Appel, Sabrina M.; Mac Low, Mordecai-Mark; McMillan, Stephen; Portegies Zwart, Simon (The astrophysical journal, 2024)
We study the evolution of populations of binary stars within massive cluster-forming regions. We simulate the formation of young massive star clusters within giant molecular clouds with masses ranging from 2 × 104 to 3.2 × 105 M ⊙. We use Torch, which couples stellar dynamics, magnetohydrodynamics, star and binary formation, stellar evolution, and stellar feedback through the Amuse framework. We find that the binary fraction decreases during cluster formation at all molecular cloud masses. The binaries’ orbital properties also change, with stronger and quicker changes in denser, more massive clouds. Most of the changes we see can be attributed to the disruption of binaries wider than 100 au, although the close binary fraction also decreases in the densest cluster-forming region. The binary fraction for O stars remains above 90%, but exchanges and dynamical hardening are ubiquitous, indicating that O stars undergo frequent few-body interactions early during the cluster formation process. Changes to the populations of binaries are a by-product of hierarchical cluster assembly: most changes to the binary population take place when the star formation rate is high, and there are frequent mergers between subclusters in the cluster-forming region. A universal primordial binary distribution based on observed inner companions in the Galactic field is consistent with the binary populations of young clusters with resolved stellar populations, and the scatter between clusters of similar masses could be explained by differences in their formation history.